2021
DOI: 10.2196/15350
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Switching to the Tobacco Heating System Versus Continued Cigarette Smoking on Chronic Generalized Periodontitis Treatment Outcome: Protocol for a Randomized Controlled Multicenter Study

Abstract: Background Smoking is a significant risk factor for periodontal disease and tooth loss, as shown in several clinical studies comparing smokers and nonsmokers. Although only a few longitudinal studies have assessed the outcome of periodontal disease after smoking cessation, they indicated that recovery after nonsurgical treatment was more successful in those who had quit smoking. As part of tobacco harm reduction strategies, substituting cigarettes with alternative, less harmful tobacco products is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Previous studies have not shown toxicity to oral fibroblasts and keratinocytes [22], however, long-term effects need to be monitored. Beneficial changes in the course of chronic generalized inflammatory periodontitis have been observed and described in people who stopped smoking cigarettes and switched to HNB products [23].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have not shown toxicity to oral fibroblasts and keratinocytes [22], however, long-term effects need to be monitored. Beneficial changes in the course of chronic generalized inflammatory periodontitis have been observed and described in people who stopped smoking cigarettes and switched to HNB products [23].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, nicotine increases the accumulation in periodontal and peri-implant tissues of Advanced Glycation and Products (AGEs), along with their receptors (RAGEs), which have been associated with the formation of ROS (reactive oxygen species), inducing, in turn, oxidative stress and metabolic changes [ 27 , 28 ] within tissues. Currently analyzed data on MMP-8 and MMP-9, specifically activated by ROS [ 78 ], revealed significantly higher levels in CS and E-Cigs compared to NS, once more supporting the contributing role of nicotine to periodontal and peri-implant tissues destruction [ 54 , 60 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco heating systems instead employ a particular heating method, reaching lower temperatures (240–350 °C) compared to traditional tobacco (>600 °C) [ 26 ], thus avoiding combustion. To our knowledge, only one study, not considering self-reported periodontitis, has presented provisional results describing more favorable periodontal treatment outcomes in HNB compared to conventional tobacco smokers [ 27 ]; however, it has been reported that HNB tobacco may potentially enhance oral epithelial cell proliferation [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…PMI have completed a randomised, controlled two-arm parallel-group multicentre Japanese study which investigated the effect of switching to a heated tobacco product on periodontal endpoints in patients with generalised chronic periodontitis (Pouly et al, 2021). A total of 172 subjects were randomised to continued conventional cigarette smoking (n=86) or switching to the heated tobacco product with all subjects completing the study.…”
Section: Future Studies On Health Effectsmentioning
confidence: 99%